Energy efficiency improvement for university college building: lighting system - Salman, Aya; Shabaro, Tasneem; Jawabreh, Razan (My University, 2019)
In this project, the confidence interval was analyzed for two types of lamps intended to be used and exchanged with the lamps used on the first floor of the College of Engineering Building at An-Najah National University, namely fluorescent and LED, Where we found that the use of LED is much better than the use of fluorescent in terms of lumen and cost, and The watt. A suggestion was made to use dimmer in addition to a sensor in order to use natural light when it is available inside the place, either to be in a sufficient rate or in different proportions according to the times of the day and the days of the year. A standard of lighting is 500 lux was approved for a classroom and by using the program VELUX Daylight Visualize 2 , 100 lux from daylight were obtained and the rest will be provided from artificial lighting, then we calculated the number of lighting units required in a classroom and accordingly several types of lighting units were chosen they are LED/MAS,LED/ Sylvania, LED/ ros and PL/sun light. And in terms of energy savings and price, Type LED/Sylvania and LED/ ros is the best from where energy saving (190 KWh/yr) and cost.